Religious Moderation and Hospitality in the Context of Jeremiah 29:7 - Silaban, Tri Oktavia Hartati; Sitorus, Herowati (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2023)
A multicultural and multireligious society demands the existence of social harmony that underlies the order of life together. Therefore, it is necessary to take proactive actions to achieve inclusive togetherness among religious communities. The teaching of Jeremiah 29:7 provides instructions for taking that proactive action. The verse instructs His people to